Análisis poblacional de mosca de la fruta (Anastrepha y Ceratitis), mediante indicadores locales de asociación espacial en las provincias de Los Ríos y Guayas - Basantes León, Erick Leonardo (2022)
Due to their high potential to attack a great diversity of species, fruit flies are considered one of the most important quarantine pests for many countries. Within the fruit fly control programs, one of the main components is the knowledge of the bio ecology based on the climatic conditions of the producing areas. This information favors the timely management of pest populations. Given the above, the present research work aimed to evaluate the population behavior of the fruit fly (Diptera: Tephritidae), through geostatistical analysis. The study was carried out by monitoring fruit flies in the period 2015 to 2019 in the province of Los Ríos and Guayas with the help of the Fruit Fly Management Project (PMMF) of the Phytosanitary Regulation and Control Agency (AGROCALIDAD).). Climate data on the trapping routes were obtained from the European Center for Medium-Range Weather Forecasts with a spatial resolution of 0.25° Latitude x 0.25° Longitude from 1980 to 2018. Data analysis was performed using box plots, histograms, scatter plots and to determine the relationship between the fruit fly population and climatic variables, the Pearson correlation coefficient was calculated. According to the results obtained, the province of Guayas presented the highest annual averages of flies/traps/day (MTD) (0.36) compared to Los Ríos (0.085). The population fluctuation of fruit flies showed that in the months of January and February the highest MTD values were reported with 0.771 and 0.508 respectively. While what, the populations decreased from the month of March (0.379) reaching low levels for the months of October, November and December (0.071). There is a high relationship between the climatic variables and the population fluctuation of the pest and in the same way a relationship between the ripening season of the host fruit trees and fruit fly populations. Therefore, studies of the population fluctuations of the different species of fruit flies, distribution of hosts and knowledge of climatic conditions are tools that favor the planning of the different measures of control and suppression of the pest.